Sustainable Crafts: Describing Conceptual Evolution Through a Bibliometric Analysis and Systematic Literature Review - Prados-Peña, María Belén; Gálvez-Sánchez, Francisco Jesús; García-López, Ana; Molina-Moreno, Valentín (Frontiers in Environmental Science, 2022)
Sustainability has been progressively incorporated into all dimensions of society as a response to the negative externalities of the traditional production model, and the craft sector has been no stranger to this. Thus, the present work constitutes a bibliometric analysis of 894 research articles from the Scopus database on sustainable crafts in the 21st century, identifying the growth trends, published articles, and the most productive journals, authors, institutions, and countries. Additionally, we have identified the main research topics that have emerged in sustainable crafts in three time periods: before the international financial crisis, the post-crisis period, and, finally, within the 2030 Agenda and the Sustainable Development Goals set out by the united nations (UN). Based on the bibliometric indicators analysed, we conclude that this research area has grown exponentially, particularly in response to the Sustainable Development Goals, increasing the abundance and diversity of the issues investigated.